Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.1 Properties of Functions - 2.1 Exercises - Page 55: 45



Work Step by Step

$f(t+1)=$ ... substitute x with $(t+1)$ and simplify $=6(t+1)^{2}-2$ $=6(t^{2}+2t+1)-2$ $=6t^{2}+12t+6-2$ $=6t^{2}+12t+4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.